Peroxidase-Mimicking Nanozymes of Nitrogen Heteroatom-Containing Graphene Oxide for Biomedical Applications - Phan Gia Le; Daesoo Kim; Jae-Pil Chung; Sungbo Cho (Biosensors)
Nanozymes constitute a rapidly advancing frontier in scientific research, attracting widespread international interest, particularly for their role in facilitating cascade reactions. Despite their initial discovery a few years ago, significant hurdles persist in optimizing their catalytic performance and substrate specificity—challenges that are especially critical in the context of biomedical diagnostics. Within this domain, nitrogen-containing graphene oxide-based nanozymes exhibiting peroxidase-mimicking activity have emerged as particularly promising candidates, owing to the exceptional electrical conductivity, mechanical flexibility, and structural resilience of reduced graphene oxide-based materials. Intensive efforts have been devoted to engineering graphene oxide structures to enhance their peroxidase-like functionality. Nonetheless, the practical implementation of such nanozymes remains under active investigation and demands further refinement. This review synthesizes the current developments in nitrogen heteroatom-containing graphene oxide nanozymes and their derivative nanozymes, emphasizing recent breakthroughs and biomedical applications. It concludes by exploring prospective directions and the broader potential of these materials in the biomedical landscape.